Immunization strategies for funding multiple inflation-linked retirement income benefits - Simões, Cláudia (2021)
Simões, C., Oliveira, L., & Bravo, J. M. (2021). Immunization strategies for funding multiple inflation-linked retirement income benefits. Risks, 9(4), [60]. https://doi.org/10.3390/risks9040060